Empowerment of Civil Servants In Improving The Quality of Public Services In Southwest Papua Province - Anace Kambu; Dian Ferriswara; Sarwani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the empowerment of civil servants and its contribution to improving the quality of public services in Southwest Papua Province, with particular focus on the Human Resources Development Personnel Agency (BKPSDM: Badan Kepegawaian Pengembangan Sumber Daya Manusia). The research employs a qualitative descriptive approach to capture and analyze empowerment practices as well as their supporting and inhibiting factors. Data collection was carried out through interviews, observations, and documentation, involving key informants such as the Head of BKPSDM and relevant staff members. The data were analyzed using the interactive model of Miles, Huberman, and Saldana, which consists of three stages: data condensation, data display, and conclusion drawing/verification. The findings reveal that empowerment practices at BKPSDM encompass structured recruitment policies for both Indigenous Papuans (OAP) and non-OAPs, systematic career development, provision of education and training programs, and implementation of fair compensation mechanisms. These initiatives are aimed at enhancing civil servants’ competencies, professionalism, motivation, and accountability, ultimately contributing to better service delivery to the public. Supporting factors identified include the existence of strong regulatory frameworks, leadership commitment, competency-based training opportunities, high internal motivation, and the establishment of a collaborative work culture. On the other hand, several inhibiting factors persist, such as limited and unequal access to training, inadequate infrastructure, frequent changes in regulations, discriminatory practices, and low levels of digital literacy among some employees. The study concludes that civil servant empowerment represents a strategic pathway to building a professional, accountable, and responsive state apparatus capable of delivering high-quality public services. To strengthen these efforts, recommendations highlight the importance of expanding training access, improving digital skills, ensuring infrastructure readiness, and maintaining inclusive and transparent policies. By addressing these challenges, civil servant empowerment can be optimized to achieve sustainable improvements in public service performance across Southwest Papua Province.